Synthesis and evaluation of hollow porous molecularly imprinted polymer for selective determination of tetracycline - Pupin, Rafael Rovatti [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP] (Springer, 2022)
A novel hollow porous molecularly imprinted polymer (HMIP) was synthesized for tetracycline determination in different matrices and the adsorption efficiency of this material was compared with the widely applied traditional (unmodified) and core-shell MIP structures. For this purpose, three different tetracycline imprinted polymers were obtained: with the reagent conditions optimized from traditional MIP, a core-shell MIP was obtained by surface polymerization of SiO2 nanoparticles (SiO2MIP). Subsequently, the silica core was removed, obtaining the hollow porous MIP. All materials were characterized by different techniques and HMIP presented higher surface area (227 m(2) g(-1)) and pore volume (0.2 cm(3) g(-1)) when compared with MIP (82.3 m(2) g(-1) and 0.09 cm(3) g(-1)) or SiO2@MIP (109 m(2) g(-1) and 0.1 cm(3) g(-1)) and the respective Non-Imprinted Polymers (NIPs). After optimizing the analysis conditions each polymer structure exhibited different kinetics and equilibrium adsorption behavior, which was related to greater or lesser porosity. HMIP presented superior results for the identification of tetracycline in adsorption experiments (maximum binding capacity of 5.6 mg g(-1) and 0.2 L mg(-1) affinity constant) and in selectivity tests. Water, synthetic urine and milk samples fortified with tetracycline were evaluated and HMIP showed recovery in the range of 74-96%. [GRAPHICS] .